CHARACTERISTICS OF STORIES IN HADĪTHS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the specific features of the stories described in the ḥadīths, their content and relevance to literary genres. The religious and educational significance of the stories, as well as the lessons and advice given through them, are analyzed. Detailed information is provided about the brief and meaningful presentation of the stories in the ḥadīths, the lessons conveyed to people through them. It also considers the role these stories play in the implementation of social and educational goals.